Mediterranean Aquaponics: Fasting and Refeeding in a Polyculture Aquaponic System - Ioannis Mitsopoulos; Anastasia Papadopoulou; Nikolaos Vlahos; Panagiotis Berillis; Efi Levizou; Eleni Mente (Applied Sciences)
The use of Mediterranean euryhaline fish and halophytes in aquaponics presents a sustainable and alternative approach to food production. The present study investigates the effect of compensatory growth on sea bass (Dicentrarchus labrax) and Baltic prawn (Palaemon adspersus) co-cultivated with the halophytic glasswort (Salicornia europaea). Three autonomous systems were established, each containing forty-five sea bass, nine Baltic prawns, and eight glasswort plants, with different feeding regimes for each treatment: (i) daily feeding (treatment A), (ii) three days of feeding per week followed by four days of fasting (treatment B), and (iii) feeding for seven days followed by seven days of fasting (treatment C). The growth performance of the fish was significantly higher in treatment B. Conversely, the feed conversion ratio (FCR) was notably higher in treatment A. As for the prawns, their final body weight and length were similar across all treatments. The glasswort plants also demonstrated significantly improved growth in treatment B. These results indicate that the incorporation of feeding and fasting cycles can be an effective feed management strategy for polyculture aquaponic systems. Additionally, food deprivation had a positive impact on the growth performance of both glasswort and prawns.